Peningkatan kompetisi PEMIRA kampus melalui calon independen - Michael Aprillino Fernandes; Abi Ahmad Yusuf; Ismail Lutfi (Universitas Negeri Malang, 2022)
The campus general election (PEMIRA) is one of the real lessons of good democracy for students. This is because through PEMIRA, students can understand all the roles and functions of components that exist in a democratic party (general elections). In the PEMIRA campus, of course, there will be many candidates from various backgrounds, including candidates who have an independent background (non-noxious and non-anti-nightmare). The participation of Independent candidates who are not from or anti-omek is a very good thing for democratic life on campus. Because in the election of the Indonesian state itself, independent candidates also get the same opportunity as party candidates to participate in the elections. In addition, the large number of independent candidates participating in the campus PEMIRA will certainly create new ideas and thoughts in campus democracy which is a miniature of the Indonesian state. However, in reality, there are many students with independent backgrounds who do not understand or still do not have the courage to advance in the campus PEMIRA as students with independent backgrounds (non-noxious and non-anti-nightmare). So that in this research, an innovation will be made that makes students with independent backgrounds dare to go forward and compete in the campus PEMIRA as students with independent backgrounds. Pemilu Raya (PEMIRA) kampus merupakan salah satu pembelajaran nyata demokrasi yang baik kepada mahasiswa. Hal ini dikarenakan melalui PEMIRA, mahasiswa dapat memahami segala bentuk peran dan fungsi komponen yang ada dalam suatu pesta demokrasi (pemilihan umum). Dalam PEMIRA kampus tentu akan banyak munculnya calon-calon dari berbagai latar belakang tak terkecuali calon yang memiliki latar belakang Independen (non omek dan non anti omek). Ikut sertanya calon Independen yang tidak berasal dari omek maupun anti omek merupakan suatu hal yang sangat baik bagi kehidupan demokrasi di kampus. Dikarenakan dalam PEMILU negara Indonesia sendiri, calon independen turut mendapatkan kesempatan yang sama dengan calon partai untuk ikut serta dalam PEMILU. Selain itu dengan banyaknya calon independen yang ikut serta dalam PEMIRA kampus tentu akan membuat munculnya gagasan dan pemikiran baru dalam demokrasi kampus yang merupakan miniatur dari negara Indonesia. Namun pada kenyataannya, banyak sekali mahasiswa berlatar belakang independen yang belum paham atau masih belum berani untuk maju dalam PEMIRA kampus sebagai mahasiswa berlatar belakang independen (non omek dan non anti omek). Sehingga dalam peneliti jam ini akan dibuatnya sebuah inovasi yang membuat mahasiswa berlatar belakang independen untuk berani maju dan berkompetisi dalam PEMIRA kampus sebagai mahasiswa berlatar belakang independen.